How does the mystery of the Chinese cat eyes relate to the evolution of vision in mammals? - Monge-Nájera, Julián (Universidad de Costa Rica, 2019)
The domestic cat, Felis catus, originated in the African wildcat species complex, a group that inhabits tropical and subtropical areas, reaching the warmer parts of Western Asia. The eyes of domestic cats are so similar to ours that human eye cells injected in cat eyes develop perfectly1. There are also differences, the phrase “all cats are grey in the dark” reflects a physiological reality: at low light levels, human eyes only use cells called rods; and rods cannot perceive colors. But cats see well and in color even in low light, thanks to a combination of rods and color sensitive cells called cones2.To understand why, we must go to the past.--READ MORE--